(untitled)
lkj &,d m".kdfVca/kh; vonkc ds thou pØ ds vkadMs+ rFkk nks m".kdfVca/kh; pØokrh rwQkuksa ds o"kZ 2002&03 dh vof/k ds vkadMs+ mPp Vh- vks- oh- ,l- ¼,- Vh- vks- oh- ,l-½ /kzqodkh; mixzgksa ,u- vks- ,- , 15 rFkk 16] ftuesa mPp lwe rjaxh; ifjKkiu bdkbZ ¼,- ,e- ,l- ;w½ yxh gqbZ gaS ls izkIr fd, x, gSa ftudk fo’ys"k.k bu rwQkuksa ds ekxZ dk iwokZuqeku djus ds fy, fd;k x;k gSA bu ekSle fokksHkksa ds 700&400 gsDVkikLdy ¼gs-ik-½ Lrj esa e/; kksHkeaMyh; m".krk e/; Lrjh ckfgokZg ds dkj.k gksrh gS tks rwQku ds 200&700 fd-eh- vkxs rd foLrkfjr gksrh gS rFkk fokksHkksa dh xfr’khyrk dk djhc 6 ls 24 ?kaVs igys iwokZuqeku djus esa iwoZ ladsrd dk dk;Z djrh gSA ;g fokksHk yxHkx mlh vk dks vuqxeu djrk gS tks e/; kksHkeaMy esa foLrkfjr ¼vkxs c<s+ gq,½ ftg okdkj m".k ks= dks dsUnz ls tksM+rk gSA e/;e rhozrk okys nks HkweaMyh; pØokrksa dh fLFkfr esa tc 7º ls 13º lsfYl;l rkieku dk m"edksj Åijh kksHkeaMyh; Lrj ¼250&200 gs-ik-½ ds djhc dsafnzr jgk ml le; vonkc dh fLFkfr esa fdlh fo’ks"k m".krk dk irk ugha pyk gSA Advanced TOVS (ATOVS), comprising the Advanced Microwave Sounding Unit (AMSU), data obtained from polar orbiting satellites NOAA 15 and 16 during the life cycle of a tropical depression and two tropical cyclonic storms during 2002-03 have been analysed to predict the track of these disturbances. The mid-tropospheric warming due to altostratus outflow from these weather disturbances in the layer 700 – 400 hPa which protrudes about 200 -700 km ahead the storm acts as a pre-cursor to predict the movement of the disturbances with a lead time of about 6 to 24 hours. The disturbance almost follows the axis connecting the centre with the warm tongue that protrudes ahead of the disturbance in the mid-troposphere. While warm core of 7 to 13° C is centered around the upper tropospheric level (250 – 200 hPa) in the case the two moderate intensity tropical cyclones, no significant warmness could be seen in the depression stage. , number=4, journal=MAUSAM, year=2006, month=Oct., pages=609–618